(3aQb GdWH dLGdjfhSs - (3LGdjfhSs
(3ChdgG (B:s
(3Ef bUO GdWH GdJeGS GdUMI EdCi Cf JYde GdCTjGA GdJi JajO GdUMI aCeG GdCTjGA GdJi JajO GdUMI EPG abOJ , agi GdCTjGA GdJi JfaY s
(3BNQgG (B:s
(3hGeG GdBf aeG bdfGg aj gPG GdHGH bO jcJai Hg GdeJYdehf, hdPdc aEfi CbWY GdcdGe aj gPG GdehVhY s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GfXQ agQS GdWH Qbe (B174s
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B167 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdCgdjI HHGQjS (B(1/1859) s
Keywords: (3GdWHs